Efficiency of SNP and SSR-based analysis of genetic diversity, population structure, and relationships among cowpea (Vigna unguiculata (L.) Walp.) germplasm from east Africa and IITA inbred lines - Desalegne, B.A.; Dagne, K.; Gedil, Melaku A; Boukar, O.; Fatokun, C.A. (Springer, 2017)
The extent of genetic diversity and relatedness of cowpea germplasm from East Africa are poorly understood. A set of 13 microsatellites (SSR) and 151 single nucleotide polymorphisms (SNPs) markers were applied to assess the levels of genetic diversity in a sample of 95 accessions of local cowpea germplasm and inbred lines of Vigna unguiculata. The average genetic diversity (D), as quantified by the expected heterozygosity, was higher for SSR loci (0.52) than for SNPs (0.34). The polymorphic information content was 0.48 for SSR and 0.28 for SNP while the fixation index was 0.095 for SSR and 0.15 for SNPs showing moderate differentiation and high gene flow among cowpea accessions from East African countries. The results of data analysis of both SSR and SNP markers showed similar clustering patterns suggesting a substantial degree of association between origin and genotype. Principal coordinate analysis (PCoA) with SSR and SNP markers showed that accessions were grouped into two and three broad groups across the first two axes, respectively. Our study found that SNP markers were more effective than SSR in determining the genetic relationship among East African local cowpea accessions and IITA inbred lines. Based on this analysis, five local cowpea accessions Tvu-13490, Tvu-6378, Tvu-13448, Tvu-16073, and 2305675 were identified to be tightly clustered sharing several common alleles with the drought tolerant variety Danila when analyzed with SSR and SNP markers. The findings will assist and contribute to future genetic diversity studies aimed at the genetic improvement of local Eastern Africa cowpea accessions for improved overall agronomic performance in general and breeding for drought tolerant in particular.